Effect of Region of Interest on Interobserver Variance in Apparent Diffusion Coefficient Measures - Bilgili, Yasemin; Unal, Birsen (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Apparent diffusion coefficient (ADC) values derived from diffusion-weighted MR imaging are useful measurements for assessment of cellular alterations in pathologic conditions of the brain. In this study, two radiologists independently quantitated ADCs and region-of interest sizes in prespecified locations of human brain to test interobserver ADC variance and the effect of varying ROI sizes on ADC differences.METHODS: Twenty-seven patients with normal MR findings underwent diffusion-weighted imaging (b value = 1000 s/mm2) on a 1.5-T system. Two radiologists independently placed two ROI areas of 22 ± 5 mm2 and 62 ± 6 mm2 (former area inside the latter area) at different sites of the brain (centrum semiovale, frontal white matter, nucleus caudatus, putamen, thalamus, substantia nigra, red nucleus, and pons) from trace images. Differences in ADC measurement obtained from each region of the brain for each radiologist and the size of each ROI were compared statistically.RESULTS: Mean ADC of prespecified areas of brain ranged between 0.673 and 0.818 mm2/s ×10−3. Interobserver variance was significant in some of the specified areas (centrum semiovale, frontal white matter, pons, substantia nigra, and red nucleus). Varying ROI sizes at the pons, substantia nigra, and red nucleus yielded statistically different ADC values.CONCLUSION: ADC values are found to be unreliable for use in assessing brain disease in some specified areas of the brain owing to interobserver variance and different ROI sizes.